2016
DOI: 10.5306/wjco.v7.i5.370
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated partial breast irradiation: Past, present, and future

Abstract: Accelerated partial breast irradiation (APBI) focuses higher doses of radiation during a shorter interval to the lumpectomy cavity, in the setting of breast conserving therapy for early stage breast cancer. The utilization of APBI has increased in the past decade because of the shorter treatment schedule and a growing body of outcome data showing positive cosmetic outcomes and high local control rates in selected patients undergoing breast conserving therapy. Technological advances in various APBI modalities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The SEER registry collects all data on patient demographics, c a n c e r i n c i d e n c e , p r i m a r y t u m o r s i t e s , c a n c e r histopathology, and survival rates. Our study cohort came from the SEER 18 Regs Custom Data (with additional treatment fields), Nov 2018Sub (1975-2016, using the SEER*Stat software provided by the National Cancer Institute. Informed consent is unnecessary because SEER data are retrospective and unidentified.…”
Section: Data Acquisition and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SEER registry collects all data on patient demographics, c a n c e r i n c i d e n c e , p r i m a r y t u m o r s i t e s , c a n c e r histopathology, and survival rates. Our study cohort came from the SEER 18 Regs Custom Data (with additional treatment fields), Nov 2018Sub (1975-2016, using the SEER*Stat software provided by the National Cancer Institute. Informed consent is unnecessary because SEER data are retrospective and unidentified.…”
Section: Data Acquisition and Patient Selectionmentioning
confidence: 99%
“…Recently, the FAST-Forward study further recommended 26 Gy in 5 fractions as a shorter course of radiotherapy, which was expected to become the standard fractionation strategy of postoperative radiotherapy for early breast cancer, because it was non-inferior to 40 Gy in 15 fractions in both local tumor control and normal tissue effects ( 13 ). Additionally, studies reported that 44–86% of ipsilateral breast tumor recurrences (IBTR) concentrated in the quadrant of primary lesions ( 14 ), leading to the emergence of the accelerated partial breast irradiation (APBI) ( 15 ). Combining the advantages of hypofractionated radiation and APBI, the concept of intraoperative radiotherapy (IORT) was proposed, which referred to the delivery of single high-dose irradiation to the tumor bed under direct view during the operation.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerated partial breast irradiation (APBI) providing radiation therapy to the tumor bed at a higher dose per fraction based on the radiobiologic equivalence is an advisable postoperative approach in properly selected elderly patients, combining advantages of a radical approach that minimizes the risk of undertreatment with efficient reduction of redundant irradiated volume [13,14]. Similarly, shortened (hypofractionated) dose fraction schedules may be more convenient for older patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the past 10 years, the possibility of treating only the tumor bed has been analyzed, as ipsilateral breast tumor recurrences (IBTR) developed in and around the tumor bed in 44–86% of cases ( 3 ), and treatment of the rest of the breast might be unnecessary. Indeed, by limiting irradiation to the area of potential recurrence by means of partial breast irradiation (PBI), much of the surrounding tissues (including the lung, heart, uninvolved ipsilateral breast) could be spared, thereby reducing toxicity and improving the cosmetic outcome ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%